The Mediating Role of R&D Intensity in the Effect of Corporate Sustainability on Financial Performance# - Ozcan, Sami; Cakir, Ozgur (International Journal of Economics and Financial Issues, 2025)
There has been a significant rise in the frequency of natural disasters such as fires, droughts, floods and tornadoes; furthermore, it has been clearly seen that epidemic preparedness throughout the world, especially in regard to the COVID-19 pandemic, can be improved by providing social supports, particularly to underdeveloped countries. Due to these developments, there is an ever greater tendency to undertake sustainability activities. Moreover, it is well known that firms make significant research and development (R&D) efforts for these activities. Hence, the current study aims to determine the mediator role of R&D activities in the impact of corporate sustainability practices on financial performance. For this purpose, panel data analysis was applied to corporate sustainability and financial data from 23 firms trading in Borsa Istanbul between 2014 and 2020. The analysis results show that corporate sustainability applications affect financial performance negatively and that this effect implicitly turns positive with the intervention of R&D efforts.